Comorbidity and health-related quality of life in Somali women living in Sweden - Demeke, Taye; Osmancevic, Amra; Gillstedt, Martin; Krogstad, Anne Lene; Angesjö, Eva; Sinclair, Håkan; El-Gawad, Gamal Abd; Krantz, Emily; Trimpou, Penelope; Landin-Wilhelmsen, Kerstin (Scandinavian journal of primary health care, 2019)
Objective: To explore the relationship between low serum vitamin D levels and comorbidity in Somali women, immigrants to Sweden. Design and setting: Cohort study in a Primary Health Care Center and a University Hospital. Subjects: Somali women skin type V, n = 114, aged 18-56 years, from latitude 0-10 ○ N, living in Sweden, latitude 57 ○ N > 2 years were compared with women from a population sample, skin type II-III, n = 69, aged 38-56 years, the WHO MONICA study, Gothenburg, Sweden. Main outcome measures: Serum (S)-25(OH)D, S-parathyroid hormone (PTH), comorbidity and Health-Related Quality of Life (HRQoL) using the Short Form-36 (SF-36) and part of the EQ-5D questionnaires. All calculations were corrected for age. Results: Vitamin D deficiency (S-25(OH)D < 25 nmol/l) was found in 73% of the Somali women and in 1% of the controls (p < .0001). S-PTH was elevated (>6.9 pmol/l) in 26% and 9%, respectively (p < .004). Somali women used less medication, 16% vs. 55%, p < .0001) but more allergy medication, 11% vs. 7% (p = .006), had fewer fractures, 2% vs. 28% (p < .0001) and lower HRQoL in 7 out of 9 scales (p < .05-.001), than native controls. There were no differences in the prevalence of diabetes mellitus, hypothyroidism, positive thyroid peroxidase antibodies, vitamin B12 deficiency, celiac disease or hypertension. Conclusions: Vitamin D deficiency was common in Somali women living in Sweden, 73%, but comorbidity was low. Both mental, and especially physical HRQoL scores were lower in the Somali women. The effects of long-lasting deficiency are unknown. Key points The aim was to explore the relationship between vitamin D deficiency (S-25(OH)D < 25 nmol/l) and comorbidity in immigrants. Vitamin D deficiency was common in Somali women living in Sweden, 73%, but comorbidity of hypothyroidism, diabetes mellitus, hypertension, fractures and use of medications was low. Both mental, and especially physical, Health-Related Quality of Life were lower in the Somali women than in native Swedish women. The effects of long-lasting deficiency are unknown.